UTILIZING CAPCUT TO FOSTER CREATIVE WRITING SKILLS IN EFL STUDENTS: A DIGITAL MEDIA APPROACH - Andhika, Dewi; Wahono, Suparwoto Sapto (University of Kuningan, 2024)
This study investigates the use of CapCut, a digital media application, to enhance the creative writing skills of EFL students. It addresses common challenges faced by students, such as difficulty in expressing ideas, lack of confidence, limited vocabulary, and low motivation in writing. By integrating CapCut into the learning process, the study aims to create an engaging and pressure-free environment for students to develop their writing skills. Using a descriptive qualitative approach, data was collected through observations, structured interviews, and narrative descriptive analysis from 15 high school students. The findings indicate that CapCut significantly improves students' productivity and creativity in writing, as evidenced by the increased number of words and the quality of paragraphs produced. Students reported a positive experience, feeling more motivated and confident in their writing abilities.